Dinamika Usia Dewasa dan Relevansinya terhadap Batas Usia Perkawinan di Indonesia: Perspektif Yuridis-Normatif: Dinamika Usia Dewasa dan Relevansinya terhadap Batas Usia Perkawinan di Indonesia: Perspektif Yuridis-Normatif - Asman, Asman (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
The age of marriage is a matter of controversy in a wedding where the determination of the age of adulthood is very diverse, both from the perspective of national law and the perspective of Islamic law. Legal experts have mixed responses to the requirements of the age of women and men and become pros and cons in marriage. This is because the age limit for marriage in Islam is very different, whereas, in Indonesian regulations, it stipulates 19 years for men and women. This article aims to examine the dynamics of adulthood and its relevance to the age limit of marriage in Indonesia. This research method takes the type of literature research with a normative-juridical approach. In this paper, researchers look for sources of Islamic law and national law based on literature from books, laws, and references that support the author’s argument. There are three results in this article. First, it is crucial to realize the equal age of marriage in the marriage law based on equality. Second, there are differences in determining the age of adulthood in several laws and regulations in Indonesia, including the Marriage Law, which causes dynamics in implementing the age limit for marriage. Third, the provision of the marriage age of 19 for men and women must be adequately enforced. The Office of Religious Affairs does not serve marriages where the prospective partner is under 19. These three ideas follow the principles of benefit, which are the references for regulations in the Islamic world (maqāshid al-syarī’ah).